Molecular architecture of Aβ fibrils grown in cerebrospinal fluid solution and in a cell culture model of Aβ plaque formation. (2nd April 2016) - Garvey, Megan; Baumann, Monika; Wulff, Melanie; Kumar, Senthil T.; Markx, Daniel; Morgado, Isabel; Knüpfer, Uwe; Horn, Uwe; Mawrin, Christian; Fändrich, Marcus; Balbach, Jochen
Abstract: Objectives : The detailed structure of brain-derived Aβ amyloid fibrils is unknown. To approach this issue, we investigate the molecular architecture of Aβ(1–40) fibrils grown in either human cerebrospinal fluid solution, in chemically simple phosphate buffer in vitro or extracted from a cell culture model of Aβ amyloid plaque formation. Methods : We have used hydrogen–deuterium exchange (HX) combined with nuclear magnetic resonance, transmission electron microscopy, seeding experiments both in vitro and in cell culture as well as several other spectroscopic measurements to compare the morphology and residue-specific conformation of these different Aβ fibrils. Results and conclusions : Our data reveal that, despite considerable variations in morphology, the spectroscopic properties and the pattern of slowly exchanging backbone amides are closely similar in the fibrils investigated. This finding implies that a fundamentally conserved molecular architecture of Aβ peptide fold is common to Aβ fibrils.